Impacto socioeconómico de la migración Venezolana a Arauca en el periodo 2017-2020 (2021)
Venezuelan migration is one of the most studied social phenomena of the last decade. Colombia, as a neighboring country of Venezuela and for sharing with this more than 2000 kilometers of border, is one of the receiving states of migrants, many of which have settled in Colombian border departments, such as Arauca. The massive influx of Venezuelans has upset the social, economic, labour and cultural life of the receiving regions. This academic work realizes that impact.